Characterization of a Ligand-attenuated Binding Site on Glycoprotein IIb/IIIa - Quinn, Martin J.; Fullard, John; Kerrigan, Steven; Harriott, Patrick; Cox, Dermot; Fitzgerald, Desmond J. (Thrombosis and Haemostasis, 2002)
We describe an epitope on the platelet integrin, GPIIb/IIIa, identified by the monoclonal antibody, 4F8, which is attenuated by small-molecule GPIIb/IIIa ligands. 4F8 did not bind to the ligand binding pocket as it did not compete with a radiolabelled antagonist, 3H-SC-52012. This indicates that the 4F8 epitope behaves as a ligand-attenuated binding site (LABS). Ligand-induced attenuation of 4F8 was an active process as it was prevented by pretreating platelets with cytochalasin D and reduced by prostaglandin E1 or inhibition of protein kinase C. Disappearance of the epitope was required for full platelet activation as 4F8 prevented platelet aggregation without inhibiting fibrinogen binding. These results suggest a model where disappearance of the 4F8 epitope is a secondary event required for full “outside-in” signaling through GPIIb/IIIa.
Keywords: Integrin; glycoprotein IIb/IIIa; conformational change; platelet; thrombosis